Plasma miR-153 and miR-223 Levels as Potential Biomarkers in Parkinson’s Disease - Wu, Li; Xu, Qian; Zhou, Mengxi; Chen, Yajing; Jiang, Chunyan; Jiang, Yuhan; Lin, Yin; He, Qing; Zhao, Lei; Dong, Yourong; Liu, Jianren; Chen, Wei (Frontiers in Neuroscience, 2022)
Background Small molecule RNAs (miRNAs) could induce downregulation of α-synuclein (SNCA) expression by binding the 3’ untranslated region of SNCA, thus playing an important role in the pathogenesis of Parkinson’s disease (PD). Recent studies suggest that SNCA-related miRNAs in saliva are promising PD biomarkers. Research on those miRNAs in plasma is rare in patients with PD. Objective To detect the plasma expression levels of three SNCA related miRNAs (miR-7, miR-153, and miR-223) in PD, and to explore their diagnostic value and associations with clinical phenotype. Methods MiR-7, miR-153, and miR-223 levels were detected in the plasma of 75 PD patients and 73 normal controls (NCs) via real-time quantitative polymerase chain reaction. The receiver operating characteristic (ROC) curves were delineated to evaluate their diagnostic value in PD. In addition, their associations with demographic, key motor, and non-motor symptoms were explored by serial scales. Results The expression levels of plasma miR-153 and miR-223 were significantly decreased in patients with PD relative to NCs. The area under the ROC curve separating PD from NCs was 63.1% for miR-153 and 86.2% for miR-223, respectively. The plasma miR-153 level in de novo PD was lower than that in treated patients (p = 0.006), its level increased gradually with disease duration (r = 0.358, p = 0.002) and Unified Parkinson’s Disease Rating Scale Part III score (r = 0.264, p = 0.022). Plasma miR-223 level was decreased in patients with clinical possible rapid eye movement sleep behavior disorder (cpRBD) compared with those without cpRBD (p < 0.001), and its level was negatively associated with RBDSQ score (r = -0.334, p = 0.003). Multiple linear regression analysis revealed that disease duration (p = 0.049) was the independently associated factor of miR-153 level; whereas, RBDSQ (p = 0.009) was related to miR-223 level in PD. Conclusion Plasma miR-153 and miR-223 levels could be potential biomarkers of PD.